Clinical Supervision Based on Spiritual Quotient to Improve the Performance of Madrasah Teachers - Siti Thowiyah; Yurnalis Etek; Sulthan Syahril; Ahmad Fauzan; Koderi Koderi (STAI Hubbulwathan Duri, 2021)
The research aimed to analyze the implementation of clinical supervision based on spiritual quotient in improving teachers' performance at State Madrasah Aliyah of Way Kanan Lampung. The research method used was descriptive qualitative. The informants in the research were principals, teachers, and supervisors. The data collections were observation, interviews, and documentation. Furthermore, it was analyzed through three stages: data presentation, data reduction, and data collection. The research showed that first, clinical supervision based on Spiritual Quotient had not been implemented, but ordinary supervision was often implemented. Second, clinical supervision based on Spiritual Quotient adapted to the diversity of teachers will impact self-awareness of their duties, so it was able to improve teachers' performance. The research implications for teachers were self-awareness, a strong desire to change for the better, and overcoming obstacles.